Effect of Frequency of Interim Financial Reporting on Information Asymmetry and Cost of Equity in Companies Listed in Jakarta Islamic Index 2012-2018 - Ahmad Rosyid; Alvita Tyas Dwi Aryani (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2020)
The purpose of this research is to find out the relationship between the frequency of interim financial reporting with information asymmetry and cost of equity for issuers in the Jakarta Islamic Index for the period 2012 to 2018. Research findings on 84 companies, namely (1) there is no relationship between the frequency of interim financial reporting with information asymmetry (2 ) there is no relationship between the frequency of interim financial reporting with the cost of equity. The absence of this relationship is caused by (1) interim financial reporting frequency data that are not different between issuers (2) research settings.